Upaya Meningkatkan Keterampilan Sains dengan Metode Pembelajaran Inkuiri pada Anak Usia Dini - Habibah; Yini Rahmawati Rosyidah; Harliana (Gayaku Publisher, 2025)
This study aims to improve early childhood science skills through the application of the inquiry-based learning method. Science skills are important from an early age because they can foster curiosity, critical thinking abilities, and scientific attitudes in children. The research method employed was Classroom Action Research (CAR), conducted in two cycles. The research subjects were 15 children in Group B at one early childhood education institution RA Miftahul Khoirot. The instrument used was a science skills observation sheet covering the abilities to observe, ask questions, and draw conclusions. The results showed a significant improvement in children’s science skills. In the pre-cycle stage, the children’s science skills only reached 19%. After the application of the inquiry method in cycle I, the skills increased to 79%. Furthermore, in cycle II, the children’s science skills reached 89%. This improvement demonstrates that through simple exploratory activities such as observing changes in objects, conducting color-mixing experiments, and planting mung beans, children became more active in asking questions, confident in expressing opinions, and able to draw simple conclusions. Thus, it can be concluded that the inquiry-based learning method is effective in enhancing early childhood science skills. This method provides opportunities for children to learn actively, enjoyably, and meaningfully through direct experiences. In addition to improving cognitive aspects, the implementation of the inquiry method also encourages the development of scientific attitudes such as curiosity, cooperation, and thoroughness, which are essential for children’s growth and development